Racism, sexism, power, and ideology - Guillaumin, Colette (Critical studies in racism and migration., 1995)
Guillaumin tackles the links between the daily materiality of social relationships and mental conventions. Materiality and ideology (in the sense of 'perception of things') are two sides of the same coin: those who are objects in social relations are so in both thought and reality.